$$\begin{array}{cl}
& \operatorname{Hom}(\operatorname{Hom}(\operatorname{Spec}(K[X_1,X_1^{-1},\cdots,X_n,X_n^{-1}]), \operatorname{Spec}(K[X,X^{-1}])), K^\times) \\
=& \operatorname{Hom}(\operatorname{Hom}(K[X,X^{-1}], K[X_1,X_1^{-1},\cdots,X_n,X_n^{-1}]), K^\times) \\
=& \operatorname{Hom}(\operatorname{Hom}(K[X,X^{-1}], K[X_1,X_1^{-1},\cdots,X_n,X_n^{-1}]), \operatorname{Hom}(K[X,X^{-1}], K)) \\
=& \operatorname{Hom}(K, K[X_1,X_1^{-1},\cdots,X_n,X_n^{-1}])~~~\text{[Yoneda]} \\
=& K[X_1,X_1^{-1},\cdots,X_n,X_n^{-1}]